Origination, Expansion, Evolutionary Trajectory, and Expression Bias of AP2/ERF Superfamily in Brassica napus - Song, Xiaoming; Wang, Jinpeng; Ma, Xiao; Li, Yuxian; Lei, Tianyu; Wang, Li; Ge, Weina; Guo, Di; Wang, Zhenyi; Li, Chunjin; Zhao, Jianjun; Wang, Xiyin (Frontiers in Plant Science, 2016)
The AP2/ERF superfamily, one of the most important transcription factor families, plays crucial roles in response to biotic and abiotic stresses. So far, a comprehensive evolutionary inference of its origination and expansion has not been available. Here, we identified 515 AP2/ERF genes in B. napus, a neo-tetraploid forming ~7500 years ago, and found that 82.14% of them were duplicated in the tetraploidization. A prominent subgenome bias was revealed in gene expression, tissue-specific, and gene conversion. Moreover, a large-scale analysis across plants and alga suggested that this superfamily could have been originated from AP2 family, expanding to form other families (ERF, and RAV). This process was accompanied by duplicating and/or alternative deleting AP2 domain, intragenic domain sequence conversion, and/or by acquiring other domains, resulting in copy number variations, alternatively contributing to functional innovation. We found that significant positive selection occurred at certain critical nodes during the evolution of land plants, possibly responding to changing environment. In conclusion, the present research revealed origination, functional innovation, and evolutionary trajectory of the AP2/ERF superfamily, contributing to understanding their roles in plant stress tolerance.